Urban bus networks’ emergency management for interdicting major emerging infectious diseases’ early transmission - Yue Pan; Ruojian Li; Hongsheng Qi (Journal of Highway and Transportation Research and Development, 2025)
In the early stages of major emerging infectious disease outbreaks, the transportation sector must identify bus stops with high relative accessibility to the risk area and interdict the accessible path, i.e., the shortest path, to regulate the spread of the outbreak within the transit system. Thus, this paper proposes a novel multi-sink shortest-path network interdiction model that incorporates accessibility measures in the reverse direction for the first time. The model consists of two steps: first, a detailed index of transit system accessibility is constructed; second, based on the accessibility definition, the accessibility path interdiction is formulated as a bi-level bi-objective programming problem. The upper-level planning aims to minimize the accessibility and traffic control cost of the transit system at bus stops in the epidemic risk area. In contrast, lower-level planning involves solving the shortest path search problem. An example network is applied to validate the proposed model and algorithm’s effectiveness, and the results show that the model is valid. Moreover, computational experiments evaluate the model’s performance in a large-scale network. The proposed model can compute the optimal decision in only 200 seconds in a real-case application.